Raise each side as a power of e to get rid of the ln:
e^(ln 2t) = e^8
2t = e^8
t = (e^8)/2
2007-05-06 14:56:09
·
answer #1
·
answered by Astronomer1980 3
·
0⤊
0⤋
ln (2t)=8 take ecponential of each side
2t=e^8 divide both sides by 2
t=1/2 e^8=1490.48
2007-05-06 15:21:27
·
answer #2
·
answered by yupchagee 7
·
0⤊
0⤋
If ln(2t) = 8, this means that 2t = e^8, so t = (1/2)e^8
2007-05-06 14:58:18
·
answer #3
·
answered by Bazz 4
·
0⤊
0⤋
Start reversing the operations.
Raise e to the power of both sides and get: e^(ln(2t)) = e^8
That simplifies to: 2t = e^8
Divide by 2 on both sides: t = (e^8)/2
2007-05-06 14:56:24
·
answer #4
·
answered by excelblue 4
·
0⤊
0⤋
divide the 8 by 2 then u get t=4
2007-05-06 14:57:05
·
answer #5
·
answered by Anonymous
·
0⤊
0⤋
ln(2t)=8
e^8 = 2t
(e^8)/2 = t
1490.478994
2007-05-06 15:05:10
·
answer #6
·
answered by Anonymous
·
0⤊
0⤋
(t) is your variable. (2t) would be 2 times T, which is your variable. Therefore, you would move the two to the opposite side by dividing it by BOTH sides, since what you do to one side you must do to the other. Therefore, on the left, the 2's would cancel, and on the right, the eight would be divided by two equaling four.
Therefore, you have t=4.
2007-05-06 14:56:21
·
answer #7
·
answered by Anonymous
·
0⤊
0⤋
raise e to each side...
e^(ln(2t))=e^8
e^ln(x)=x soooo
2t=e^8
divide each side by 2 to get
t = (e^8)/2
2007-05-06 14:57:10
·
answer #8
·
answered by Napper 2
·
0⤊
0⤋
ln(y)=x means y=exp(x )
ln(2t)=8
2t=exp(8)
t=(1/2)exp(8)
=1490.5 (approx)
2007-05-06 14:58:48
·
answer #9
·
answered by gudspeling 7
·
0⤊
0⤋
easy.
ln(2t) = 8
exp(ln(2t)) = exp(8)
2t = exp(8)
t = exp(8)/2
2007-05-06 14:57:57
·
answer #10
·
answered by electric 3
·
0⤊
0⤋